Self-Assembly and Superlubricity of 2D Material Auto-Kirigami Ribbons - Sinnott, Pierce (Trinity College Dublin. School of Physics. Discipline of Physics, 2025)
Auto-kirigami describes a novel self-assembly process in graphene involving thermodynamically driven tearing, substrate peeling and sliding of graphene, all occurring spontaneously in ambient conditions. Following rupture of mechanically exfoliated graphene sheets by small amplitude sheared nanoindentation, this process results in formation of folded graphene auto-kirigami ribbons with micrometre scale lengths. This growth is enabled by the low sliding friction of structural superlubricity between graphene ribbons and their host graphene sheets in incommensurate contact. In this work, auto-kirigami ribbons are studied and characterised by atomic force microscopy (AFM), particularly using the high resolution PeakForce Quantitative Nanomechanical Mapping Mode. Using this mode, ordered stripe hydrocarbon adsorbates of atmospheric origin are observed ubiquitously on graphene surfaces, which strongly modify the friction of these surfaces. Time resolved formation and dynamics of stripe friction domains are studied. Crucially, we further demonstrate that these adsorbates are also present in the graphene-graphene interface of ribbons, in buried graphene-graphene interfaces within graphitic flakes and at graphene-substrate interfaces, with significant implications for the cleanliness of van der Waals structures. Despite this, we show that superlubricity can persist in stripe-contaminated ribbon interfaces. Rupture of graphene sheets as a necessary precursor to auto-kirigami is studied by small amplitude sheared indentation nucleation using a 2D indentation contact system, with the contributing effects of graphene layer number, shear oscillation frequency and strain rate on rupture depth examined. We also develop a novel method of nucleating auto-kirigami ribbons which can be performed using only a standard AFM. This facile, high yield method does not require an applied small amplitude shearing oscillation, which massively extends the applicability of auto-kirigami nucleation and growth. Successful auto-kirigami is also demonstrated on graphene produced by chemical vapour deposition using both nucleation methods, facilitating large scale application of auto-kirigami without the area and yield limitations of micromechanical exfoliation of graphene. While auto-kirigami is inhibited by the presence of residual PMMA contaminants on CVD materials, we review and perform thermal annealing, catalytic cleaning, and mechanical micro-cleaning by AFM on these contaminants. Finally, towards developing auto-kirigami ribbons as nanoelectromechanical devices, we induce reversible growth of ribbons by mechanical manipulation with an AFM and explore methods towards electrical control of graphene auto-kirigami ribbons.
APPROVED
Keywords: Graphene; Atomic Force Microscopy; Nanoindentation; Auto-kirigami; Self-assembly; PeakForce Quantitative Nanomechanical Mapping; Adsorbates